A Monte Carlo study of the chlorophyll fluorescence emission and its effect on the leaf spectral reflectance and transmittance under various conditions - Susila, Petr; Naus, Jan (Photochemical & photobiological sciences, 2007)
Spectral hemispherical reflectance R(lambda) and transmittance T(lambda) are affected by chlorophyll (Chl) fluorescence which may complicate the evaluation of optical parameters of leaves. Measured Chl a fluorescence spectral emission F(lambda) is itself affected by several distortion effects on the leaf level (fluorescence reabsorption, secondary fluorescence, inner filter, surface and subsurface reflections etc.). In this work we propose a Monte Carlo photon transport (MCPT) model capable for treating a variety of optical distortion effects on the leaf level. In the forward mode the model decouples R(lambda), T(lambda) and their fluorescence contributions FR(T)(lambda). To obtain the absorption and scattering spectra of the leaf, utilized in the forward modeling, we have suggested an inversion procedure employing the experimental R(lambda), T(lambda). The attention was paid on the correction of the leaf absorption and scattering spectra caused by the optical effects on the sample level including Chl fluorescence contribution to measured R(lambda), T(lambda).
Keywords: Chlorophyll; Monte Carlo Method; fluorescenční spektrometrie; Plant Leaves; metoda Monte Carlo; Spectrometry, Fluorescence; chlorofyl; listy rostlin